2021
DOI: 10.3390/cancers13153720
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Novel Covered Stent without External Thread Fixation for Anastomotic Leakage after Total or Proximal Gastrectomy for Gastric Cancer

Abstract: A thread-fix stent entails long hospitalization and patient discomfort. We aimed to evaluate the efficacy of a novel stent with silicone-covered outer double layers without external fixation (Beta stent) for anastomotic leakage after total or proximal gastrectomy. The outcomes were compared between gastric cancer patients who underwent stent placement using a thread-fix stent between 2014 and 2015 (Thread-Fix Group) and those who received a Beta stent in the succeeding period until October 2018 (Beta Stent Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Curcio et al reported the efficacy of endoscopic stents for anastomotic leakage after esophagojejunostomy following total gastrectomy in 2010 [ 19 ]. In the past, Ultraflex Stents or plastic stents were used; in recent years, however, HANAROSTENT® or Niti-S™ has been used in the reported cases [ 10 , 20 ]. A feature of these stents is that the diameters of both ends are slightly larger than that of the center, providing a structure that is highly adherent to the esophageal lumen and does not easily migrate.…”
Section: Discussionmentioning
confidence: 99%
“…Curcio et al reported the efficacy of endoscopic stents for anastomotic leakage after esophagojejunostomy following total gastrectomy in 2010 [ 19 ]. In the past, Ultraflex Stents or plastic stents were used; in recent years, however, HANAROSTENT® or Niti-S™ has been used in the reported cases [ 10 , 20 ]. A feature of these stents is that the diameters of both ends are slightly larger than that of the center, providing a structure that is highly adherent to the esophageal lumen and does not easily migrate.…”
Section: Discussionmentioning
confidence: 99%
“…The "Niti-S Beta" stent is a novel stent designed to minimize the risk of stent migration and to simplify the removal of stents for leakage or fistula after bariatric surgery. They have 92% healing rate from the first stent placement, higher than for thread-fix stents (53.8%), with a 7% migration rate [84].…”
Section: Endoscopic Stentingmentioning
confidence: 92%
“…The stent migration rate was 13% for conventional stents with clips and 17% for suture fixation. 25 On the other hand, another retrospective study investigating the use of Beta oesophageal stents in staple line leaks showed a migration rate of 32%, with no significant decrease in the stent migration rates. 26 In this case, despite using an anti-migratory stent, the stent migrated distally after 8 weeks.…”
Section: Self-expanding Metal Stentsmentioning
confidence: 97%